SOURCES OF RESISTANCE IN THE ADOPTION OF ECO-FRIENDLY LIGHTING PRODUCTS: A STUDY OF TECHNICAL DOUBTS, EXAGGERATED NARRATIVES, AND BRAND DISTRUST - Didit Darmawan; M. Najib Zakariya (Asosiasi Dosen Muda Indonesia, 2026)
This literature study aims to analyze the sources of consumer resistance to environmentally friendly lighting products, focusing on doubts about technical specifications, resistance to exaggerated green promotion narratives, and distrust of brand motivations behind environmental campaigns. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that technical doubts arise from complex information confusing average consumers and past negative experiences with energy-efficient products. Resistance to promotional narratives is triggered by greenwashing practices, exaggerated unverifiable claims, and patronizing language. Distrust of brand motivations stems from perceptions that companies are more motivated by profit than environmental concern, reinforced by inconsistencies between campaigns and business practices. These three sources of resistance are interconnected and mutually reinforcing, creating significant barriers to adoption of environmentally friendly products. Understanding these resistance sources is essential for manufacturers and policymakers to design more authentic and effective communication strategies. This study contributes theoretically to enriching green marketing literature with a consumer resistance perspective and practically provides foundations for manufacturers in simplifying technical information, avoiding exaggerated claims, and building trust through consistent practices.